Mindsets religiöser Pluralität als Faktor in der (islamischen) Religionslehrer*innenbildung - Kamcili-Yildiz, Naciye; Mauritz, Gerrit; Reis, Oliver; Wittke, Annika (Theo-Web. Zeitschrift für Religionspädagogik)

Pluralisation of Theologies at European Universities

Säkular und religiös: Herausforderungen für Christentum und Islam

Lesen lernen von Aufgabentexten - Dröse, Jennifer; Prediger, Susanne (Sprachbildender Mathematikunterricht in der Sekundarstufe - ein forschungsbasiertes Praxisbuch)

Physik in der Lehrerinnen- und Lehrerbildung. Auf dem Weg zu empirisch fundierten Curricula - Reinhold, Peter; Riese, Josef (Handbuch Lehrerinnen- und Lehrerbildung)

Die Messung der Fähigkeit zur Unterrichtsplanung im Fach Physik mit Hilfe eines standardisierten Performanztests - Schröder, Jan; Riese, Josef; Vogelsang, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst (Zeitschrift für Didaktik der Naturwissenschaften)
Zusammenfassung Die Unterrichtsplanung stellt eine zentrale berufliche Anforderung an (Physik‑)Lehrkräfte dar. Bereits im Lehramtsstudium sollen grundlegende Fähigkeiten zur Unterrichtsplanung erworben und im Rahmen von schulpraktischen Phasen erprobt bzw. erweitert werden. Unklar ist jedoch, inwieweit das professionelle Wissen, das Lehramtsstudierende in ihren fachlichen, fachdidaktischen und erziehungswissenschaftlichen Studienteilen erwerben, tatsächlich bei der Planung von Fachunterricht genutzt wird. Ebenso gibt es nur punktuelle Erkenntnisse über die Entwicklung der Fähigkeit zur Unterrichtsplanung im Lehramtsstudium. Um diese Fragen zu klären, sind Messverfahren erforderlich, die die Fähigkeiten zur Unterrichtsplanung valide erfassen können und die gleichzeitig ökonomisch auswertbar sind, um Fallzahlen realisieren zu können, die auch kleine Effekte auflösen. Bisherige Ansätze, die reale Handlungsproben der Unterrichtsplanung (z. B. schriftliche Unterrichtsentwürfe) untersuchen, stehen vor der methodischen Herausforderung, dass die Generierung eines Fähigkeitsmaßes höchst anspruchsvoll ist, da reale Planungen individuell sehr unterschiedlich angelegt sind und vielen Randbedingungen unterliegen, die statistisch kaum kontrollierbar sind. In diesem Beitrag wird daher ein sogenannter Performanztest zur Erfassung der Fähigkeit zur Unterrichtsplanung vorgestellt und diskutiert. Ein Performanztest ist ein Verfahren, in dem in einem realitätsnahen Setting Handlungen unter standardisierten Rahmenbedingungen simuliert werden. Neben der theoriegeleiteten Entwicklung des Instruments und Vorstudien zur Sammlung von Validitätsargumenten werden auch erste Ergebnisse dargestellt, die aus Erhebungen vor und nach einem Praxissemester an vier Universitäten in drei Bundesländern resultieren ( N = 174 Unterrichtsplanungen). Dabei stellt sich das Testverfahren als ausreichend sensitiv heraus, um für N = 68 Testpersonen (ca. 20 % Dropout) erwartungstreu eine signifikante Zunahme des Testscores während des Praxissemesters, welches als Lerngelegenheit angenommen werden kann, zu messen.

Development of Prospective Physics Teachers’ Professional Knowledge and Skills during a One-Semester School Internship - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Reinhold, Peter; Schecker, Horst; Schröder, Jan (Student Learning in German Higher Education)

Professional knowledge affects action-related skills: The development of preservice physics teachers’ explaining skills during a field experience - Kulgemeyer, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph (Journal of Research in Science Teaching)
Keywords: Education

Mindsets guter Lehre in Beziehung zu den Mindsets religiöser Pluralität - Kamcili-Yildiz, Naciye; Reis, Oliver; Mauritz, Gerrit; Hillebrand, Miriam; Wittke, Annika (Theo-Web. Zeitschrift für Religionspädagogik, 19)

The Story of Mary as a Feminine Counterpart to the Story of Joseph - Haghani Fazl, Mohammad (Religious Inquiries, 9)

Adhesion of HVOF-Sprayed WC-Co Coatings on 316L Substrates Processed by SLM - Tillmann, Wolfgang; Hagen, Leif; Schaak, Christoph; Liß, J.; Schaper, Mirko; Hoyer, Kay-Peter; Aydinöz, Mehmet Esat; Garthe, Kai-Uwe (Journal of Thermal Spray Technology)
Abstract Different studies have been demonstrated that the surface integrity of substrate bulk materials to be coated has a significant impact on the adhesion of thermally sprayed coatings. It is known that the surface integrity of parts processed by selective laser melting (SLM) differs from those obtained from bulk materials. Although 316L stainless steel is among the most investigated material for SLM, the adhesion of thermally sprayed coatings on 316L stainless steel substrates processed by SLM has not been studied yet. This study aims at evaluating the effect of various mechanical pre-treatments onto 316L stainless steel substrates processed by SLM and their effect on the adhesion of high velocity oxy-fuel (HVOF)-sprayed WC-Co coatings. To differentiate between topographical effects and residual stress-related phenomena, a stress-relief heat treatment of the SLM substrates served as a reference throughout the investigations. The differently pre-treated SLM substrates were investigated with regard to the surface roughness and residual stresses. For the HVOF-sprayed SLM composites, Vickers interfacial indentation tests were conducted to assess the resulting coating adhesion. The findings demonstrated that the HVOF-sprayed WC-Co coatings predominantly exhibit good adhesion to the SLM 316L substrates. However, it was found that the stress state in the SLM 316L substrate surface is more likely to affect the adhesion of the WC-Co coating, while the substrate surface roughness showed a marginal effect.
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Condensed Matter Physics

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Characterization of Phase Transformations During Graded Thermo-Mechanical Processing of Press-Hardening Sheet Steel 22MnB5 - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Metallurgical and Materials Transactions A)
Abstract Safety-relevant components in automobiles require materials that combine high strength with sufficient residual ductility and high-energy absorption. A graded thermo-mechanical treatment of the press-hardening steel 22MnB5 with graded microstructure can provide a material with such properties. Different austenitization temperatures, cooling and forming conditions within a sheet part lead to the development of microstructures with mixed phase compositions. To determine the resulting phase contents in such graded processed parts, a large number of dilatometric tests are usually required. With a non-contact characterization method, it is possible to detect local phase transformations on an inhomogeneously treated flat steel specimen. For press-hardening steel after heat treatment and thermo-mechanical processing, correlations between austenitization temperature, hot deformation strain, microstructure, and hardness are established.

New Twin-Roll Cast Al-Li Based Alloys for High-Strength Applications - Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko; Belejová, Sára; Králík, Rostislav; Bajtošová, Lucia; Křivská, Barbora; Hájek, Michal; Cieslar, Miroslav (Metals)
Al-Li based alloys are attractive materials for the aerospace industry. The twin-roll casting of such materials could provide properties not achievable by conventional direct-chill casting and downstream processing methods due to significantly higher solidification rates. An Al-Li-Cu-Mg-Zr alloy was twin-roll cast with the same alloy containing a small addition of Sc. The microstructure of as-cast materials and the influence of Sc on the behavior of the alloy at elevated temperatures were studied by means of light and electron microscopy and by resistivity measurements. A fine-grained structure was formed during twin-roll casting, but several surface and internal defects were found on the strips, which should be suppressed by a further adjustment of the casting conditions. The addition of Sc had a positive effect on grain size uniformity and microstructure stabilization at elevated temperatures, as shown by the precipitation of a fine dispersion of coherent Sc- and Zr-containing precipitates.

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Zinc oxide (ZnO) hollow spheres with defined morphology and micro-/nanostructure are prepared by a hydrothermal synthesis approach. The materials possess fine-leaved structures at their particle surface (nanowall hollow micro spheres). Morphology control is achieved by citric acid used as an additive in variable relative quantities during the synthesis. The structure formation is studied by various time-dependent ex situ methods, such as scanning electron microscopy, x-ray diffraction, and Raman spectroscopy. The fine-leaved surface structure is characterized by high-resolution transmission electron microscopy techniques (HRTEM, STEM), using a high-angle annular dark field detector, as well as by differential phase contrast analysis. In-depth structural characterization of the nanowalls by drop-by-drop ex situ FE-SEM analysis provides insight into possible structure formation mechanisms. Further investigation addresses the thermal stability of the particle morphology and the enhancement of the surface-to-volume ratio by heat treatment (examined by N2 physisorption).

Strain parameters at hot rolling of aluminum strips reinforced with steel netting - Stolbchenko, Mykhailo; Makeieva, Hanna; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Journal of Sandwich Structures & Materials)
This experiment studied the strain parameters of rolling an aluminum matrix when wire netting is inserted between aluminum layers. During the experiment, two types of stainless steel fabric netting oriented parallel and diagonal to the rolling axis were placed between two aluminum strips and rolled. Multiple rolling processes were performed in which the temperature and pressure on the material were varied to produce bonding of matrix layers. During the study, the following main investigations were made: strain on areas of longitudinal and transverse cross sections of the composite was measured; stretching and ovalization of net wiring and changes in the net cell angles were determined; mechanical properties of composites along the rolling direction were tested. The main contradiction resulting from this experiment was as follows: the contact pressure required for the bonding of aluminum layers produces extreme tensile strain on the inserted net wires, reducing the mechanical properties of the reinforcing net and thus reducing properties of the entire composite. Optimal results in the longitudinal tension tests were achieved by using strips with diagonally oriented net-reinforcement.

Characterization of the fatigue behaviour for SAE 1045 steel without and with load-free sequences based on non-destructive, X-ray diffraction and transmission electron microscopic investigations - Wu, Haoran; Bill, T.; Teng, Z.J.; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Starke, Peter (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Tribo-mechanical properties and adhesion behavior of DLC coatings sputtered onto 36NiCrMo16 produced by selective laser melting - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Stangier, Dominic; Hagen, Leif; Schaper, Mirko; Hengsbach, Florian; Hoyer, Kay-Peter (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Degradable silver‐based alloys - Andreiev, Anatolii; Hoyer, Kay-Peter; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

The mechanical properties of rolled wire-reinforced aluminum composites at different strain values - Stolbchenko, Mykhailo; Frolov, Yaroslav; Makeieva, Hanna; Grydin, Olexandr; Tershakovec, Michael A.; Schaper, Mirko (Mechanics of Advanced Materials and Structures)

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)

Adhesion of HVOF-Sprayed WC-Co Coatings on 316L Substrates Processed by SLM - Tillmann, Wolfgang; Hagen, Leif; Schaak, Christopher; Liß, Jan; Schaper, Mirko; Hoyer, Kay-Peter; Aydinöz, Mehmet Esat; Garthe, Kai-Uwe (Journal of Thermal Spray Technology)
Abstract Different studies have been demonstrated that the surface integrity of substrate bulk materials to be coated has a significant impact on the adhesion of thermally sprayed coatings. It is known that the surface integrity of parts processed by selective laser melting (SLM) differs from those obtained from bulk materials. Although 316L stainless steel is among the most investigated material for SLM, the adhesion of thermally sprayed coatings on 316L stainless steel substrates processed by SLM has not been studied yet. This study aims at evaluating the effect of various mechanical pre-treatments onto 316L stainless steel substrates processed by SLM and their effect on the adhesion of high velocity oxy-fuel (HVOF)-sprayed WC-Co coatings. To differentiate between topographical effects and residual stress-related phenomena, a stress-relief heat treatment of the SLM substrates served as a reference throughout the investigations. The differently pre-treated SLM substrates were investigated with regard to the surface roughness and residual stresses. For the HVOF-sprayed SLM composites, Vickers interfacial indentation tests were conducted to assess the resulting coating adhesion. The findings demonstrated that the HVOF-sprayed WC-Co coatings predominantly exhibit good adhesion to the SLM 316L substrates. However, it was found that the stress state in the SLM 316L substrate surface is more likely to affect the adhesion of the WC-Co coating, while the substrate surface roughness showed a marginal effect.

Adhesion of HVOF-Sprayed WC-Co Coatings on 316L Substrates Processed by SLM - Tillmann, W.; Hagen, L.; Schaak, C.; Liß, J.; Schaper, Mirko; Hoyer, Kay-Peter; Aydinöz, M. E.; Garthe, Kai-Uwe (Journal of Thermal Spray Technology)
Abstract Different studies have been demonstrated that the surface integrity of substrate bulk materials to be coated has a significant impact on the adhesion of thermally sprayed coatings. It is known that the surface integrity of parts processed by selective laser melting (SLM) differs from those obtained from bulk materials. Although 316L stainless steel is among the most investigated material for SLM, the adhesion of thermally sprayed coatings on 316L stainless steel substrates processed by SLM has not been studied yet. This study aims at evaluating the effect of various mechanical pre-treatments onto 316L stainless steel substrates processed by SLM and their effect on the adhesion of high velocity oxy-fuel (HVOF)-sprayed WC-Co coatings. To differentiate between topographical effects and residual stress-related phenomena, a stress-relief heat treatment of the SLM substrates served as a reference throughout the investigations. The differently pre-treated SLM substrates were investigated with regard to the surface roughness and residual stresses. For the HVOF-sprayed SLM composites, Vickers interfacial indentation tests were conducted to assess the resulting coating adhesion. The findings demonstrated that the HVOF-sprayed WC-Co coatings predominantly exhibit good adhesion to the SLM 316L substrates. However, it was found that the stress state in the SLM 316L substrate surface is more likely to affect the adhesion of the WC-Co coating, while the substrate surface roughness showed a marginal effect.

Characterization of the fatigue behaviour for SAE 1045 steel without and with load-free sequences based on non-destructive, X-ray diffraction and transmission electron microscopic investigations - Wu, Haoran; Bill, Tobias; Teng, Zhenjie; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Starke, Peter (Materials Science and Engineering: A)

Tribo-mechanical properties and adhesion behavior of DLC coatings sputtered onto 36NiCrMo16 produced by selective laser melting - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Stangier, Dominic; Hagen, Leif; Schaper, Mirko; Hengsbach, Florian; Hoyer, Kay-Peter (Surface and Coatings Technology)

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)

Influence of Microstructure in Near‐Surface Areas of Feedstocks on the Bond Strength of Roll Bonded Aluminum Clads - Grydin, Olexandr; Matzelt, Manuel; Andreiev, Anatolii; Frolov, Yaroslav; Schaper, Mirko (Advanced Engineering Materials)

Degradable silver‐based alloys - Andreiev, Anatolii; Hoyer, Kay-Peter; Grydin, Olexandr; Frolov, Yaroslaw; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)

Dialektatlas Mittleres Westdeutschland (DMW) - Methodik, Akquise, Exploration und Analyse - Wallmeier, Nadine; Kuhmichel, Katrin; Gehrke, Gero; Sauermilch, Stephanie (Niederdeutsches Wort)

Messung der Fähigkeit zur Unterrichtsplanung bei Lehramtsstudierenden - Schröder, Jan; Vogelsang, Christoph; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Ursachen für Veränderungen des physikdidaktischen Wissens im Studium - Joswig, Ann-Kathrin; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Basismodelle in Unterrichtsplanungen im Praxissemester Physik - Buschhütter, David; Mutschler, Tanja; Schröder, Jan; Riese, Josef; Borowski, Andreas (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Entwicklung eines Fachpraktikums im Techniklehramt - Ermel, Dorothee; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Wie entwickeln sich Wissen und Fähigkeiten im Physiklehramtsstudium? - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Estimation of acoustic wave non-linearity in ultrasonic measurement systems - Claes, Leander; Steidl, Carolin; Hetkämper, Tim; Henning, Bernd (arXiv.org)

Does Informational Equivalence Preserve Strategic Behavior? Experimental Results on Trockel’s Model of Selten’s Chain Store Story - Duman, Papatya (Games)
The purpose of this study is to experimentally test Trockel’s game, which is a modelling of the classical Chain Store Game (CSG), and determine whether one of the two theories of Equality and Deterrence may better account for the observed behavior. The CSG is an example of a simple game in extensive form where the actual behavior of well-informed players cannot be expected to agree with the clear results of game theoretical reasoning. To explain the disagreement between the theory and the expected behavior, Trockel’s game is proposed as an alternative modelling of the scenario. The existence of more than one equilibrium in Trockel’s game opens a door for reputation building. This study is the first attempt to experimentally test this alternative game with the same purpose. According to my data, there is some evidence in favor of both Equality and Deterrence Hypotheses. However, since the strategies compatible with the Equality Hypothesis are played more frequently, I observe some patterns which share the same intuition with the Deterrence Hypothesis.
Keywords: Applied Mathematics; Statistics; Probability and Uncertainty; Statistics and Probability

Gemeinsam Forschung gestalten. Handreichung zu partizipativer Forschung - Lutz, Katharina; Offergeld, Jana; Freymuth, Nina; Arp, Anna Liza

Frühe alltagsintegrierte mathematische Bildung. Eine Einleitung - Bruns, Julia; Vogtländer, A. (Frühe alltagsintegrierte mathematische Bildung. Handreichung für Lehrende)

Situative Beobachtung und Wahrnehmung angehender frühpädagogischer Fachpersonen im Bereich Mathematik – Entwicklung und Validierung eines Testinstruments - Bruns, Julia; Strahl, Carolin; Gasteiger, Hedwig (Unterrichtswissenschaft)
Zusammenfassung Frühe mathematische Bildung findet in der Kindertagesstätte insbesondere in spontanen Alltagssituationen statt. Damit diese Alltagssituationen zu natürlichen Lernsituationen für die Kinder werden, müssen (angehende) frühpädagogische Fachkräfte zunächst das mathematische Potenzial in diesen Situationen erkennen. Diese Fähigkeit zur situativen Beobachtung und Wahrnehmung ist bisher unzureichend erforscht, was unter anderem auf begrenzte Methoden zur standardisierten Erfassung dieses Konstrukts zurückzuführen ist. Um diesem Bedarf zu begegnen, wurde das videobasierte Testinstrument Vimas_num zur Erfassung der Fähigkeit zur situativen Beobachtung und Wahrnehmung angehender frühpädagogischer Fachpersonen im Bereich Mengen und Zahlen entwickelt. Auf der Grundlage von drei aufeinander aufbauenden Studien wird die Validität verschiedener Aspekte der Testwertinterpretation untersucht. Die Ergebnisse geben Hinweise auf die Validität der Testwertinterpretation in Bezug auf den Testinhalt, die interne Struktur des Tests und die Zusammenhänge mit theoretisch verbundenen Konstrukten.
Keywords: Education

Interaktionen in mathematischen Spielsituationen in Kindertagesstätte und Familie - Meyer, Lena; Tabeling, Laura; Gasteiger, Hedwig; Bruns, Julia (Beiträge zum Mathematikunterricht 2020)

Adaptionshandlungen von Multiplikatorinnen und Multiplikatoren zur frühen mathematischen Bildung – Beschreibung und Bewertung aus fachbezogener Perspektive - Bruns, Julia; Schopferer, Theresa; Gasteiger, Hedwig (Journal für Mathematik-Didaktik)
Zusammenfassung Die Implementation früher mathematischer Bildung in Kindertagesstätten kann durch fachdidaktische Fortbildungen für frühpädagogische Fachkräfte unterstützt werden. Um Fachkräfte in der Breite zu erreichen, erscheint ein scaling up Ansatz geeignet, bei dem aufbauend auf das Fortbildungskonzept EmMa – Erzieherinnen und Erzieher machen Mathematik Multiplikatorinnen und Multiplikatoren qualifiziert werden. Dabei ergibt sich die Herausforderung, dass Fortbildende im Elementarbereich kaum mathematisches und mathematikdidaktisches Wissen mitbringen. Der Kontext dieser Studie ist der scaling up Prozess der Fortbildung EmMa unter diesen Umständen. Das Erkenntnisinteresse liegt in der Beschreibung und Bewertung der Adaptionshandlungen der Multiplikatorinnen und Multiplikatoren. Für die Bewertung der Adaptionen werden zwei Kriterien herangezogen: (1) das Kriterium der Präzision, das die Vollständigkeit und Klarheit der Inhalte umfasst und (2) das Kriterium der fachlichen Korrektheit, das durch das Ausbleiben fachbezogener Fehler beschrieben wird. Analysiert werden dabei die theoretischen, fachbezogenen Phasen der von Multiplikatorinnen und Multiplikatoren durchgeführten Fortbildung zur frühen mathematischen Bildung, da davon ausgegangen wird, dass insbesondere diese theoretischen Inhalte für diese Gruppe von Multiplikatorinnen und Multiplikatoren eine Herausforderung darstellen. Zur Untersuchung wurde eine videogestützte, qualitative Feldstudie mit N = 8 Fällen durchgeführt. Mit Hilfe der qualitativen Inhaltsanalyse wurden die Adaptionshandlungen der Multiplikatorinnen und Multiplikatoren charakterisiert und hinsichtlich ihrer Präzision und der fachlichen Fehler in diesen Adaptionen analysiert. Dabei zeigte sich, dass der eigenständige Umgang mit den mathematischen und mathematikdidaktischen Inhalten des Fortbildungskonzepts EmMa trotz intensiver Unterstützung anspruchsvoll und bei vielen Multiplikatorinnen und Multiplikatoren mit fachbezogenen Fehlern verbunden ist. Implikationen dieser Ergebnisse für die weitere Forschung werden diskutiert.

Situational Perception in Mathematics (SPiM)—Results of a Cross-Country Study in Austria and Norway - Bruns, Julia; Carlsen, Martin; Eichen, Lars; Erfjord, Ingvald; Hundeland, Per Sigurd (Mathematics Education in the Early Years)

Mathematisches Fachwissen von frühpädagogischen Fachpersonen im Spannungsfeld zwischen Disziplin- und Praxis - Bruns, Julia (Beiträge zum Mathematikunterricht 2020)

“Why don’t you make a drawing?" Motivation and strategy use in mathematical modelling - Schönherr, Johanna; Blomberg, J.; Schukajlow, S.; Rellensmann, J. (Proceedings of the 44th Conference of the International Group for the Psychology of Mathematics Education: PME)

Measuring and investigating strategic knowledge about drawing to solve geometry modelling problems - Schönherr, Johanna; Schukajlow, S.; Leopold, C. (ZDM – Mathematics Education)

Paderborner Qualitätsstern zur Einschätzung der Kooperation im Übergang Kita – Grundschule. Herausgegeben von: Höke, Julia; Büker, Petra, Ogrodowski, Jana & Vollmann, Britta. Unter Mitarbeit von Alina Bruyn und Theresa Driller. Dieses Instrument liegt seit 2021 ebenfalls in vollständiger englischer Übersetzung vor: https://blogs.uni-paderborn.de/pq3-international/ - Herding, Jana

Zur Bedeutung von Integrationserfahrungen in der Grundschulzeit aus der Retroperspektive junger Erwachsener: eine Interviewstudie - Herding, Jana; Ogrodowski, J. (Diversität und soziale Ungleichheit. Herausforderungen an die Integrationsleistung der Grundschule. Jahrbuch Grundschulforschung)

Digitale Transformationsprozesse in der beruflichen Benachteiligtenförderung – erste Ergebnisse einer qualitativen Studie - Schemmer, Susanne Jutta (Digitalisierung am Übergang Schule Beruf. Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung)

Lebenswelten und soziale Netzwerke von jungen Geflüchteten und Zugewanderten am Übergang in Ausbildung und Beruf - Schemmer, Susanne Jutta; Heisler, Dietmar (bwp@Berufs-und Wirtschaftspädagogik – online, (24.06.2020))

Semantic-based End-to-End Learning for Typhoon Intensity Prediction - Zahera, H.M.A (Arxiv)